Educação, indústria cultural e ressentimento no seriado Todo Mundo Odeia o Chris - Magalhães, Gianni Marcela Boechard (2016)
This dissertation reflects on the action of the mass media in the formation of subjectivities process in children and adolescents. The object of study is the tv series Everybody hates Chris, a tv show with high rates of audience on Brazilian television, and indicated by 24 out of 25 students of an elementary school class in Vila Velha county. The problem of this research concerns the production of resentment validated by the media, in order to analyze what this affection can trigger in social relations. It starts with the following hypothesis: a) feelings of inferiority can be produced and/or exacerbated by the cultural industry mediation, that formats the meaning of life by the media and contributes to the process of sermiformation (Halbildung), which can be one of the main reasons for the adaptation of the subjects; b) the lack of development of the past, whether individual or collective, can be one of the factors that tend to perpetuate the beliefs of individuals, especially what regards to the formation of subjectivities. From some dialogues of characters from the show, it is proposed to analyze the concept of resentment, as well as its possible consequences. Of a theoretical-analytical nature, from a qualitative approach, the research refers to the Critical Theory of Society from Theodor Adorno, in dialogue with aspects of Nietzsche's philosophy as well as the tradition of psychoanalytic theory. From Adorno‟s studies, it was possible to verify that the cultural industry has a decisive role in the orchestration of tastes and desires of human beings and in promoting the ideology that being submissive is the only possible condition for a particular class. However, when the resentful individuals can no longer sublimate hate, they turn against someone, and it's devastating. One possible solution, according to Adorno, is the realization of a crystalline elaboration of the past, in a way to rise to the level of consciousness, the remains abandoned in the debris of history - individual and collective - put itself in search of subjective and objective source that determines the existence of actions that mean the present time